Analysis of the Assessment of Geo-Tourism Potential as Added Economic Value and Attractiveness of Pampang Cultural Village, Samarinda, East Kalimantan - Reananda Putra; Muhammad Aaqil; Muhammad Zaky Fahrozi; Wisnu Ismunandar (Sean Institute, 2025)
Geotourism is a tourism activity towards panorama and geology, which can be of a conservation nature with the types of natural resources of a region in order to develop insight and understanding of the process of phenomena that occur in nature as a driver of the regional and national economy. Pampang Village is a tourist destination and center of social and cultural activities, which is often used for traditional events. Enjoying Pampang is not only enough through its cultural attractions, Pampang has several charms that are not yet widely known, namely the Pampang River, and the exotic Pampang waterfall. Therefore, based on the potential of geotourism in the form of geological objects and supported by natural beauty, the research area can be developed into a geotourism area. This research method is carried out in three stages, namely a literature review on geotourism, a survey of geotourism locations, initial observations of geotourism that have the feasibility to be assessed as an economic factor and geoheritage. In the qualitative assessment using 4 types of assessments that will then be applied, namely the assessment of scientific values, assessment of educational values, assessment of tourism values, assessment of degradation risk values. Based on the results of data analysis conducted on each geosite that shows the feasibility as a medium class geotourism. In the assessment of science values, the Pampang River geosite received a weighting of 58.75% and Pampang Waterfall 58.75%. For educational values, the Pampang River received a weighting of 45% and Pampang Waterfall 47.5%. For tourism values, the Pampang River received a weighting of 35% and Pampang Waterfall 37.5%. For degradation risk values, the Pampang River received a weighting of 78.75% and Pampang Waterfall 78.75%. The total weighting for each geosite was categorized as moderate with a weighting of 217.5, and the Pampang River waterfall received a weighting of 220.5.